Pernicious Effects of Toe Sucking Habit in Children. (29th November 2016) - Pai, Deepika; Kumar, Saurabh; Kamath, Abhay T.; Bhaskar, Vipin
Abstract : Digit sucking is common nonnutritive sucking habit in childhood. However it is unusual to find toe sucking habit in children. We report a case of a seven-year-old child sucking great toe of the left foot. The child was referred by her paediatrician for dental evaluation due to her complaint of recurrent episodes of pyrexia. A dental evaluation was warranted as no particular system contributed to such recurrent episodes of fever in this child. Although dental examination did not reveal any cause for recurrent episodes of pyrexia, as a part of routine history taking we discovered that this child indulges frequently in sucking the great toe of her left foot since infancy. Any nonnutritive sucking habit is considered deleterious; this habit also caused significant effect on the child's dentofacial structures, sucked toe, and her general health. Hence the treatment plan was formulated for immediate cessation of habit. Appropriate interception of habit and timely orthodontic intervention led to not only early interception of cross-bite but also decrease in pyrexial episodes. This case report describes the pernicious effects of toe sucking habit and its relevance to recurrent pyrexia in children.